Combating Corruption: Problems and Challenges in Indonesia - Fakhrizy, Ivan Muhammad (Law Research Review Quarterly, 2021)
Corruption has been regarded as commonplace, under the pretext of "being in line with procedures". Corruptors no longer have a sense of shame and fear, instead of showing off their demonstrative corruption results. A crime corruption is a violation of social rights and economic rights of society, so that crime corruption can no longer be classified as ordinary crimes but has become a crime extra-ordinary crimes. So in the effort to eradicate it seems still require the struggle is heavy and can no longer be done "as usual", but it takes "extraordinary ways" (extraordinary crimes). Given the actions by law enforcement officials, it is hoped that the crime of corruption is not increasing expanding. If law enforcement is not as good as it is today, crime is growing, corruption more rampant, bribery cases happening everywhere, abuse of narcotics, and so can only be controlled from a penitentiary. Finally, as well as any existing legislation on ultimately depending on law enforcement officers.